Retinal Ischemia as a Presenting Ocular Sign of Neurofibromatosis Type 2 - Binbin Zhao; Yan Yan (Case Reports in Ophthalmological Medicine)
Purpose. Specific retinal abnormalities of neurofibromatosis type 2 (NF2) commonly include retinal astrocytoma and combined hamartoma of the retina and retinal pigment epithelium. Vasculopathy is an uncommon manifestation of NF2. We reported an NF2 patient presenting with retinal ischemia. Observations. An 18-year-old healthy Chinese female with acute decreased vision. The fundus examination and optical coherence tomography revealed optic disc hamartoma in the right eye and paracentral acute middle maculopathy (PAMM) and cotton wool spot indicating retinal ischemia in the left eye. Brain MRI showed bilateral acoustic neuroma, parasellar meningioma, and cervical extramedullary tumor. The genetic test confirmed the diagnosis of NF2. Conclusions and Importance. Our case suggests that retinal ischemia could be the presenting sign of NF2. NF2 could be associated with retinal vasculopathy in addition to retina tumors.